ANALISIS PENGARUH PERSEPSI LABEL HALAL, KUALITAS PRODUK, DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN PRODUK HALAL : Studi Pada Konsumen Starbucks di Tangerang Selatan - Cikal Rivaldi (2020)
This research is a quantitative study that aims to determine the effect of perceptions of halal labels, product quality, and service quality on purchasing decisions. The population in this study were visitors who purchased drinks at STARBUCKS coffee shop, South Tangerang. The sample size was taken as many as 75 respondents, with non-probability sampling technique sampling with purposive sampling method. Data collection was carried out through questionnaires. The analysis technique used is the PLS (Partial Least Square) analysis method with SmartPLS 3.2.8 software. The results of this study indicate that Halal Label perception does not significantly influence purchasing decisions, Product Quality has a significant effect on purchasing decisions, Service Quality has a significant effect on purchasing decisions. The results of the determinant coefficient of the halal label perception variables, product quality and service quality have an influence of 58.4% on purchasing decisions and the other 41.6% are influenced by other variables.